Reflections on Police Law Enforcement and Civil Rights Protection based on Constitutional Perspective - Zhu, Yingying (Journal of Theory and Practice of Social Science, 2023)
How to better protect the basic rights of citizens in today's era has increasingly become the focus of attention. In order to guarantee that citizens' rights are not violated in the process of police law enforcement, the police should cultivate constitutional thinking and rule of law thinking, to ensure that the exercise of power abides by the boundaries of the constitution, and to fully protect the constitutional rights of citizens is the effective way to solve the conflict between state power and citizens' rights.